2019
DOI: 10.1097/mao.0000000000002020
|View full text |Cite
|
Sign up to set email alerts
|

Can a Chronic BPPV With a History of Trauma be the Trigger of Symptoms in Vestibular Migraine, Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), and Whiplash Associated Disorders (WAD)? A Retrospective Cohort Study

Abstract: Background: In patients with chronic benign paroxysmal positional vertigo (BPPV), i.e., chronic vestibular multicanalicular canalithiasis (CVMCC), abnormal signals are transmitted from diseased labyrinths via the healthy vestibular nuclei complex to their end organs. The vestibulo-thalamo-cortical reflex as proposed in vestibular migraine is just one of these reflexes. In a group of patients diagnosed with CVMCC otolith repositioning maneuvers specific for each semicircular canal (SCC) ameliorated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Among 24 patients with Ménière's disease (Bjorne & Agerberg, 2003), 75% reported neck and shoulder pain, and 50% reported pain in the face or jaws. Similar results were found in two studies on BPPV (Iglebekk et al, 2013;Tjell et al, 2019) where 82%-87% reported neck pain, and 13% reported widespread/generalized pain. In the same studies, peri-/retroorbital pain was reported by 67%-74%, and temporomandibular pain by 59%.…”
Section: Oto-vestibular Diagnosessupporting
confidence: 89%
See 1 more Smart Citation
“…Among 24 patients with Ménière's disease (Bjorne & Agerberg, 2003), 75% reported neck and shoulder pain, and 50% reported pain in the face or jaws. Similar results were found in two studies on BPPV (Iglebekk et al, 2013;Tjell et al, 2019) where 82%-87% reported neck pain, and 13% reported widespread/generalized pain. In the same studies, peri-/retroorbital pain was reported by 67%-74%, and temporomandibular pain by 59%.…”
Section: Oto-vestibular Diagnosessupporting
confidence: 89%
“…In most cases dizziness passes quickly, but in 30%–50% of the cases the symptoms become persistent (Cousins et al., 2017 ; Godemann et al., 2005 ; Heinrichs et al., 2007 ; Kammerlind et al., 2005 ). Experiencing persistent dizziness can be exhausting and disabling with concomitant ailments such as musculoskeletal pain (Malmström et al., 2021 ), and psychological comorbidity (Lahmann et al., 2015 ), resulting in reduced quality of life and sick leave (Iglebekk et al., 2013 ; Neuhauser et al., 2008 ; Tjell et al., 2019 ). In some cases dizziness eventually results in long‐lasting conditions, such as persistent postural‐perceptual dizziness (PPPD) (Bittar & von Söhsten Lins, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, participants described fatigue as unpredictable in occurrence, intensity, and duration and feeling a loss of control of the body. Patients with whiplash-associated disorders suffer from fatigue, sleep disturbance, and cognitive deficits similar to ME/CFS patients (15). Chronic fatigue can be unpredictable and triggered by anxiety and emotional trauma (16).…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that PTH may result from abnormal signaling in any part of the trigeminal nerve system. A similar study suggests that minor trauma of the head, neck, and craniocervical junction could have a major impact on the vestibular system at variable sites, [24] which may explain the abnormal signals transmitting from a diseased labyrinth to the healthy, normally functioning vestibular nuclei complex in multiple chronic canal benign paroxysmal positional vertigo [25]. Because both ATN and ZTN are proximal to the vestibular nuclei complex, the mechanisms may be the closest analogy to PTH.…”
Section: Discussionmentioning
confidence: 91%